Occurrence of gastrointestinal parasites in domestic yaks in Sikkim - RAHAMAN, H; PAL, P; BANDYOPADHYAY, S (The Indian Journal of Animal Sciences, 2010)
Occurrence of gastrointestinal parasites in domesticated yaks of North and East districts of Sikkim was studied during the year 2001 to 2008. Of the 4,792 animals examined, 991 (20.68%) were found positive for different gastrointestinal parasites. The overall occurrence of different parasites recorded was strongyles (17.36%), Strongyloides spp. (4.34%), coccidia (4.55%), Toxocara spp. (2.25%), Trichuris spp. (2.88%), amphistomes (0.52%) and Moniezia spp. (3.07%). The infestation was more in Sub-Alpine low humid area (29.34%) as compared to Alpine dry zone ((19.0%) and Cold Desert zone (10.05%). The faecal egg counts (eggs per gram, epg) of nematodes ranged from 100 to 2 900, with higher loads during rainy and post-rainy seasons. The infection was higher in calf (1–5 months) and the parasites mostly recorded were Haemonchus spp., Toxocara spp. and Eimeria spp. The seasonal distribution of parasitism indicated a higher percentage of infestation in autumn (26.02%) and summer (21.57%) as compared with spring (20.65%) and winter (13.73%). On coproculture of positive samples, the nematode infestations in order of prevalence were Haemonchus, Bunostomum, Oesophagostomum and Nematodirus spp.